2018
DOI: 10.1101/272914
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A projection specific logic to sampling visual inputs in mouse superior colliculus

Abstract: Summary 10The superior colliculus is an important node in the visual system that receives inputs from the retina and 11 distributes these visual features to various downstream brain nuclei. It remains unknown how these 12 circuits are wired to enable specific and reliable information processing. Here the retinal ganglion cells at 13 the beginning of two such circuits, one targeting the pulvinar and the other the parabigeminal nucleus, 14were labeled using mono-synaptically restricted rabies tracing. Instead of… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
26
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(28 citation statements)
references
References 66 publications
2
26
0
Order By: Relevance
“…For example, direction-selective neurons in the superficial layers of the mouse SC inherit their selectivity from the retina, and the population of ll direction-selective neurons declines with depth in the SGS, consistent with the projection patterns of direction-selective ganglion cells (Barchini et al, 2018;Huberman et al, 2008Huberman et al, , 2009Inayat et al, 2015;Kay et al, 2011;Shi et al, 2017). Furthermore, transsynaptic labeling in mice identified a biased sampling of retinal ganglion cell types by different kinds of SC projection neurons, suggesting again that the information carried by different retinal ganglion cell types is maintained in parallel SC channels (Reinhard et al, 2019).…”
Section: Laminar Organizationsupporting
confidence: 58%
“…For example, direction-selective neurons in the superficial layers of the mouse SC inherit their selectivity from the retina, and the population of ll direction-selective neurons declines with depth in the SGS, consistent with the projection patterns of direction-selective ganglion cells (Barchini et al, 2018;Huberman et al, 2008Huberman et al, , 2009Inayat et al, 2015;Kay et al, 2011;Shi et al, 2017). Furthermore, transsynaptic labeling in mice identified a biased sampling of retinal ganglion cell types by different kinds of SC projection neurons, suggesting again that the information carried by different retinal ganglion cell types is maintained in parallel SC channels (Reinhard et al, 2019).…”
Section: Laminar Organizationsupporting
confidence: 58%
“…In the last decade, enormous advances have been made in understanding functional and anatomical connectivity of the CNS [ 16 , 17 , 18 ]. Thanks to these techniques, a detailed sketching of the neural repertoire underlying sensory-guided defensive behaviors in the mouse is in process and substantial advances have been made in the last few years [ 6 , 9 , 19 , 20 , 21 , 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…In the rodent brain, SC-originating shortcuts have genetically identifiable cell types that causally and independently evoke distinct behavioural responses to visual signs of threat or prey. The SC-LP-amygdala pathway, which mediates freezing 14 and prey detection 23 , receives input from retinal ganglion cells that prefer small, slow stimuli (for example, a distal flying predator), whereas the SC-parabigeminal nucleus-amygdala pathway, which triggers escape 15 and prey pursuit behaviour 23 , receives input from retinal ganglion cells that prefer large, fast stimuli (for example, a proximal collision) 24 . A recent optogenetic study has demonstrated that silencing the mediating node of either pathway (that is, the LP or the parabigeminal nucleus) results in a dominance of the other path's behavioural output 25 .…”
Section: Parallel Paths For Defensive Behaviourmentioning
confidence: 99%